The Canadian State and Aboriginal Land Claims: Temagami in an Institutional Perspective - Holmes, James Clifford Paul (My University, 1991)
This thesis uses the land claim of the Teme-Augama Anishnabai in Northern Ontario to explain why some land claims endure over decades with no apparent solution in sight. A neo-institutionalist framework, drawing heavily on the work of March and Olsen, focuses the study on the institutions of the Canadian state and the decision-making processes contained therein. Realizing that adjudication and negotiation represent two very distinct decision-making processes, the thesis explains why each process has been unable to effectively deal with some aboriginal land claims. To help explain these failures, the concept of cultural imprint is introduced. Cultural imprint refers to the values that a particular culture may imbue into institutions. This thesis also recognizes that comprehensive land claims (a claim based on aboriginal title) constitute a unique demand on institutions. Such claims suggest that a consensual relationship between aboriginal peoples and non-aboriginal society does not exist. Thus comprehensive land claims are interpreted as exogenous demands on the state. In this context adjudication is concluded to be an inherently inferior process when it is confronted with comprehensive land claims. Although negotiation is considered to be the more desirable process, the current structure of the negotiation process is completely inadequate in Canada. The thesis concludes that some land claims will not be resolved until an improved negotiation process, where aboriginal peoples can bargain as equals, is established.
Keywords: Political Science; Political Science